An Illustrated Guide to Flying - Schiff, Barry (Aviation Supplies & Academics, Incorporated, 2022)
Inspired by the effortless soaring of birds, humans have taken to wing as the safest, fastest, and most enjoyable way to travel. An Illustrated Guide to Flying explains the principles and practice of flying with concise critical facts, supported with prolific illustrations and photographs, covering basic flight maneuvers, aircraft engines and flight instruments, navigation, weather, types of aircraft, traffic control, flight rules, and more.This is an exciting introduction to flying for aspiring pilots of all ages, revealing the mysteries of flight and explaining how pilots deal with their aircraft and the elements through which they fly. Either as a student, passenger, or future pilot, the reader will enter a fascinating new world that offers challenge, fun, and adventure.